Typology of Communication Strategies in the Discourse of Social Advertising - M. V. Terskikh (Научный диалог, 2020)
A typology of strategies, tactics and techniques used in the discourse of social advertising is proposed in the article. The relevance of modeling the tools of communicative impact in social advertising is determined by the persuasive nature of the discourse of social communications, as well as the insufficient development of this issue in the scientific literature. The author of the article relies on the studies of linguists who proposed the classification of communicative strategies used in commercial advertising, as well as in the discourse of socio-political newspapers. The material for analysis was the polycode texts of Russian and foreign social advertising (outdoor advertising, social videos, as well as social photo projects posted on Instagram). The result of the study was a model of communicative strategies and tactics that constitute the discourse of social advertising. Since the effect of persuasiveness is achieved, among other things, by using different types of semiotic codes in the advertising text, special attention is paid to the verbal and visual implementation of the selected strategies, tactics and techniques. The author comes to the conclusion that the frustration strategy based on tactics of escalating negative emotions , shocking with facts and negative forecasting is the basis for the discourse of social advertising. Moreover, the main part of the identified strategies and tactics is invariant for the media discourse as a whole.